Financial literacy of students: The case study of UiTM in Rzeszów, Poland - Karolina Palimąka (Financial Internet Quarterly, 2020)
The article focuses on the phenomenon of financial literacy of students. Financial literacy is treated as a combination of financial knowledge and the decision-making process where one has to make a choice based on experience and theory. The aim of this paper is to draw attention to the essence of financial literacy, including knowledge of banking(especially of young people). For this purpose, a literature review was used. Own research complements the topic as a case study, where the author verifies whether students assess their knowledge in a way that corresponds to reality and verifies whether students need to expand their financial knowledge sorely necessary nowadays. The survey was completed by 380 students from University of Information Technology and Management in Rzeszów, of both economic and non-economic field of studies. There are some unexpected results, for example the most important is that students from a financial field of studies end up with worse results than their peers from the non-financial degree programs.
Keywords: I21; I22; 330; financial literacy; financial awareness; financial knowledge of student